The Association Between Breast Cancer and Blood-Based Methylation of S100P and HYAL2 in the Chinese Population - Yin, Qiming; Yang, Xiaoqin; Li, Lixi; Xu, Tian; Zhou, Wenjie; Gu, Wanjian; Ma, Fei; Yang, Rongxi (Frontiers in Genetics, 2020)
Previous work has shown that DNA methylation in peripheral blood may be associated with malignancy, however these studies have mainly been conducted within Caucasian populations. Here, we investigated the association between blood-based methylation of S100P and HYAL2 and breast cancer (BC) via mass spectrometry in two independent case-control studies of the Chinese population with a total of 351 BC cases and 427 cancer-free female controls. In Study I, in which subjects had an average of 45 years, hypomethylation of S100P showed a protective effect for women ≤ 45 years (six out of nine CpG sites, p < 0.05), but not for women > 45 years. In contrast, hypomethylation of HAYL2 was not correlated with BC in women ≤ 45 years, but was a risk factor for women > 45 years (three out of four CpG sites, p < 0.05). We proposed an age-dependent correlation between BC and methylation of S100P and HYAL2, and performed further validation in Study II with older subjects (average age = 52.5 years), where hypomethylation of both S100P and HYAL2 was a risk factor for BC (p < 0.05 for 10 CpG sites) as reported in Caucasians who develop BC around 55 years old. Together with the observation that Chinese cancer-free females having variant basal methylation levels comparing to Caucasians, we assumed that blood-based methylation might be modified by ethnic background, hormone status and lifestyles. Here, we highlighted that the epigenetic biomarkers warrant validations when its application in variant ethnic group is considered.